Fifteen years of lessons from the Seascape approach: A framework for improving ocean management at scale. Issue 6 (3rd May 2021) - Murphy, Shannon E.; Farmer, Ginny; Katz, Laure; Troëng, Sebastian; Henderson, Scott; Erdmann, Mark V.; Corrigan, Colleen; Gold, Barry; Lavoie, Christian; Quesada, Marco; Díazgranados Cadelo, María Claudia; Guzmán Mora, Ana Gloria; et al.
Abstract: Seascapes are large, multiple‐use marine areas, defined scientifically and strategically, in which government authorities, private organizations, and other stakeholders cooperate to conserve the diversity and abundance of marine life and promote human well‐being. This approach has been applied by global nonprofit partnerships in five seascapes across eight countries and has drawn on the practical experience of more than 250 partners over 15 years. These experiences have helped define the Seascape approach, consisting of nine essential elements, for achieving effective ocean governance and management from local to regional levels. Lessons learned relate to using integrated planning frameworks, community‐led and locally owned initiatives, and a network of partners and a "backbone" organization for effective Seascape planning and design; promoting diversification in funding sources, private sector engagement, and the transition of nonprofit roles to ensure durability of a Seascape; and ensuring Seascape outcomes are measured through robust monitoring and evaluation frameworks and communicated effectively. Seascapes are unique in their ability to create a pathway toward sustainable development. To ensure support and amplification of the approach, they must align with diversified funding opportunities and global priorities outlined in international United Nations conventions focused on sustainable development and ocean health. Abstract : In this article, we overview the Seascape approach and present results to date from five Seascapes spanning parts of eight countries. This approach has been implemented over 15 years and has involved the experience of Seascape practitioners and a network of over 250 partners. Lessons and best practices can help inform current and future Seascape initiatives, and can be useful as countries and other actors seek to expand effective ocean management and create a pathway toward sustainable development.